Autonomy and Power : the Dynamics of Class and Culture in Rural Bolivia - Lagos, Maria L. (University of Pennsylvania Press, 2016)
Maria L. Lagos supplies a fine-grained ethnographic and historical analysis of the intersecting dynamics of class and culture in Tiraque, a province in the highlands of Cochabamba, Bolivia.
Keywords: Indians of South America -- Bolivia -- Tiraque (Cordillera) -- Politics and government.; Indians of South America -- Land tenure -- Bolivia -- Tiraque (Cordillera); Indians of South America -- Bolivia -- Tiraque (Cordillera) -- Social conditions.; Peasants -- Bolivia -- Tiraque (Cordillera); Rural poor -- Bolivia -- Tiraque (Cordillera); Tiraque (Cordillera, Bolivia) -- History.; Tiraque (Cordillera, Bolivia) -- Social conditions.; Tiraque (Cordillera, Bolivia) -- Politics and government.; SOCIAL SCIENCE -- Anthropology -- General.; Indians of South America -- Land tenure; Indians of South America -- Politics and government; Indians of South America -- Social conditions; Peasants; Politics and government; Rural poor; Social conditions; Bolivia -- Tiraque (Cordillera); History